The complete mitochondrial genomes and phylogenetic analysis of two Nycteribiidae bat flies (Diptera: Hippoboscoidea) - Megan L. Porter; Holly Lutz; Mireille Steck; Rebecca A. Chong (Mitochondrial DNA. Part B. Resources, 2022)
We sequenced the complete mitochondrial genomes of two bat fly species within the Nycteribiidae (Diptera: Hippoboscoidea) – Dipseliopoda setosa (Cyclopodiinae) and Basilia ansifera (Nycteribiinae). Both mitogenomes were complete and contained 13 protein-coding genes, 22 tRNAs, and two rRNAs. Relative to the inferred ancestral gene order of dipteran mitochondrial genomes, no rearrangements were identified in either species. There were large differences in size between the two genomes, with D. setosa having a larger genome (19,164 bp) than B. ansifera (16,964 bp); both species had larger genomes than two previously published Streblidae bat fly species (e.g., Paradyschiria parvula and Paratrichobius longicrus). The increased genome sizes were due to expansions in the control region and the non-coding region downstream of the light-strand origin of replication. Additional differences between the two mitogenomes included a significantly longer cox3 gene in B. ansifera and a longer nad1 gene in D. setosa. Interestingly, both genomes also had the lowest GC content (D. setosa – 15.9%; B. ansifera – 17.0%) of any available Hippoboscoidea mitochondrial genome (18.8–23.9%). These mitogenomes represent the first sequences from species within the bat fly family Nycteribiidae. The sequence data here will provide a foundation for continued studies of genome evolution more generally within obligate blood-feeding ectoparasites, and specifically for the bat flies as vectors of significant ‘bat-associated’ viruses and microorganisms.